PB10 Safe Elderly Emergency Discharge (SEED) project: determining best practice for safe discharge of the older emergency patient. (19th March 2012) - Lowthian, J; Cameron, P; Smit, D; Newnham, H; Hunter, P; Brand, C; Barker, A; Banerjee, J; Cooke, M
Abstract : Background and Objectives: Increasing numbers of older patients presenting for emergency hospital care is a major worldwide concern. The fastest growth is in people aged ≥65 years representing 18% of all presentations. An ED visit for older people is a sentinel health event that can lead to substantial functional decline and adverse outcomes. This age group present with more complex conditions, consume more resources, have longer ED stays, are more likely to be admitted, have long hospital stays, and a higher rate of re-presentation. This will increase with population ageing. Although social/psychological support is often required there is little evidence this occurs in a systematic coordinated manner. SEED aims to Determine whether current models of emergency care ensure safe discharge and facilitate optimal health outcomes for older patients. Develop a tailored evidence-based care framework applicable to Australian and international settings. Methods: PHASE 1: Review of best practice : Systematic review of best evidence for models of care for older patients in ED or short stay units. PHASE 2: Evaluation of methods for assessment of unsafe discharge risk : Evaluation of effectiveness of discharge risk screening tools designed to reduce risk of unsafe discharge. PHASE 3: Audit current practice against published best practice : Prospective process mapping of the patient care journey in 3 EDs in Australia and UK: during ED stay and post-discharge, with monitoring of health outcomes in the following 6 months. Expected Outcomes: Development of an Older Patient Care Service Framework : Redesign of emergency care for older patients. To include: Development of policy and principles of management, care pathways, and performance improvement measures. Validation of an unsafe discharge screening tool in an Australian & English cohort. Development of a stream-lined care pathway. Reduced ED length of stay. Improved patient experience. Safe discharge with optimisation of health outcomes, reduced unplanned emergency re-presentations; reduced need for higher level residential care; reduced unplanned deaths. Reduced emergency demand and improved patient flow.